Efektifitas Ekstrak Cabai Merah (Capsicum annum L) Terhadap Mortalitas Kutu Daun (Aphis gossypli) Pada Tanaman Cabai - Maria Nindatu; Debby Moniharapon; Stesiana Latuputty (Agrologia, 2016)
Red chili (Capsicum annuum L.) is an important commodity and has high economic value in Indonesia. Problems encountered in the cultivation of chili in Indonesia decreased productivity due to pests attack. Aphids (Aphis gossypii) is a major pest that attacks the chili leaves. This research was aimed to determine the effectiveness of ered pepper (Capsicum annuum L.) extract on mortality of aphids; especially  the effective concentration and LC50 of red chili extract on mortality of aphids (Aphis gossypii). This research tested five concentration of chili extract treatments with four replicates each. Third instar of nymphs were fasted for 30 minutes before, then nymphs attached to the chili leaves were trasferred into the petri dish. Each petri dish filled with 10 nymph of Aphis gossypii. Red chili extract of 3%, 5%, 7% and 9% sprayed 3 times on the nymph. Mortality rate was calculated 24 hours after application. The results showed that the extract of red pepper were effective to kill aphids nymphs, the lowest mortality was  35% at a concentration of 3% and the highest one was up to 92.5% at a concentration of 9%. Effective concentration (LC50) extract of red pepper that cause 50% of the mortality of the aphids for 24 hours of testing was  7.46%.